Students acceptance on document sharing through learning management system - Mat Yamin, Fadhilah; Wan Ishak, Wan Hussain; Ibrahim, Amlus (2014)
Learning Management System (LMS) is a vital tool that can be used to support teaching and learning process.To date many institutions of higher learning have employed LMS as a platform to manage their e-learning program. Typically various tasks can be performed through LMS such as delivering and managing the course materials.However, due to the limitation of computer and internet facility, access to the LMS can sometime become trouble some especially when uploading and downloading large documents.In this paper we focus our study on document sharing which is one of the typical features in LMS.This study adapted Unified Theory of Acceptance and Use of Technology(UTAUT) to assess students' perception towards document sharing through LMS.The results reveal that students have positive perception towards LMS.Furthermore, students have indicate that they are keen on continue using the LMS in their learning.